Reconstruction of the Role of Bhabinkamtibmas in Village Food Security: Socio-Legal Analysis of Authority and Social Stability - Andri Ritanto; Harmono Harmono (Ann Publisher, 2026)
Background. This research departs from the assumption that village food security is determined not solely by production and distribution but also by the social stability that underpins it. In this context, the presence of Bhabinkamtibmas as a police officer at the village level shows an interesting role, although it is not explicitly regulated within the legal framework of food security. Aims. This research aims to analyze how these roles are carried out, examine the basis of their legal authority, and identify obstacles that arise in practice. Methods. The method used is a socio-legal approach that combines normative analysis of laws and regulations with empirical data from interviews in Gegesik Village, Cirebon Regency. Result. The results of the study show that Bhabinkamtibmas are not involved in the technical aspects of food management but rather act as actors of social stabilization through preventive, mediative, and facilitative functions, especially in maintaining a conducive environment for aid distribution and reducing potential conflicts. However, this role remains within the realm of implicit authority and has not been normatively integrated into food security policies. Conclusion. This condition shows that there is a gap between collaborative practice in the field and legal construction that is still sectoral. Implementation. Therefore, it is necessary to strengthen institutional coordination and integrate social security dimensions into the formulation of village food security policies to make them more responsive and sustainable.